THE EFFECTIVENESS OF ANIMAL FLASH CARD MEDIA IN INTRODUCING ENGLISH VOCABULARY FOR CHILDREN AGED 5-6 YEARS - Kusmiati, Kusmiati; Yustika Rini, Ratu; Dayurni, Popi; Mulyawan, Galuh (LPPM Universitas Bina Bangsa, 2026)
Study This aim for know the effectiveness of animal flashcard media in introduce vocabulary​​ English for children age 5-6 years. The method used is pre- experimental with one pretest-posttest design. Subjects study totaling 10 children Group B in an Integrated Islamic Kindergarten Annida. Data collection techniques use test mastery vocabulary before and after​ treatment. The pretest results showed that all over child is at in category low with an average score of 17.5. After given treatment learning using animal flashcard media, posttest scores increased with an average of 35.6. A total of 5 children is at in category tall and 5 children is at in very high category. The t-test results show existence significant difference​ between the pretest and posttest. The results of the N-Gain test reached the value of 32.3% which is included in high. Besides that, the results of the Pearson correlation test show very strong and significant relationship between use of flashcard media with improvement vocabulary, with r value = 0.966 and p = 0.000. With thus, it can It can be concluded that animal flashcard media is effective. in introduce vocabulary​​ English for children age 5-6 years